(3GdUdM Hjf GdENhGf aj Mce EHGMI GdONGfs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ESJYeGd ONGf dJJf fGaYkG HJLajag GdQWhHGJ GdRGFOI ai GdGLSGe heMdddkG deG JcGKa ai GdUOQ ef dRhLI GdHdZe hegVekG Yf GdeYOI Kbd GdWYGe hWGQO ddQjGM dGeMJHSI ai GdYQhb s
(3BNQgG (B:s
(3aCMcGe Gddg JYGdi hGVMI HjfI ceG bGd GdfHi Udi Gddg Ydjg hSde GdMdGd Hjf hGdMQGe Hjf aEVQGQ GdEfSGf faSg hEdMGb GdCPi HgG MQGe HCi TF cGf hGdCTjGA GdeHGMGJ eHGMGJ Ydi eGgi Ydjg dGJJZjQ hdGJJHOd hdcf GdJVQQ dGjYQa hdG jJMbb Ydi hLg jHfi Ydgj GdMs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B70s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs